Selective excitation of LP01 mode in multimode fiber using solid-core photonic crystal fiber - Amphawan, Angela; Nedniyom, Benjaporn; Al Samman, Nashwan M. A. (Taylor & Francis Group, 2014)
To address the overwhelming bandwidth increase in premise backbones, an attractive alternative for selective mode excitation in multimode fiber (MMF) using solid-core photonic crystal fiber (PCF) is presented. The power coupling efficiency, differential mode delay, and bit-error rate performance of several structural designs of solid-core PCF waveguides are investigated for the selective excitation of mode LP01 in a MMF. The achieved coupling efficiency into mode LP01 is above 90% for PCF profiles with seven ring.